Clinical application of ultrasound-guided acupotomy combined with platelet-rich plasma in the treatment of carpal tunnel syndrome - Ji, Guofei; Chen, Wenxian (Frontiers in Surgery, 2025)
BackgroundThis study aims to assess the impact of ultrasound-guided acupotomy combined with platelet-rich plasma (PRP) in treating carpal tunnel syndrome (CTS).MethodsA total of 72 CTS patients admitted to our hospital from June 2022 to December 2024 were divided into the control group and study group. The control group received ultrasound-guided acupotomy combined with dextrose 5% water treatment, while the study group received ultrasound-guided acupotomy combined with PRP therapy. The clinical efficacy, degree of pain, wrist joint function, median nerve conduction indicators, incidence of complications, and activities of daily living (ADL) were compared in both groups.ResultsCompared with the control group, the study group had a higher total effective rate along with a lower incidence of complications (P < 0.05). Compared with before treatment, the visual analog scale (VAS), Boston carpal tunnel questionnaire (BCTQ)-symptom severity scale (SSS), and BCTQ-functional status scale (FSS) scores declined, and the ADL score was elevated in both groups at 1, 3, and 6 months following treatment (P < 0.05). Relative to the control group, the study group had lower VAS, BCTQ-SSS, and BCTQ-FSS scores and higher ADL scores at 1, 3, and 6 months following treatment (P < 0.05). Relative to before treatment, the values of sensory nerve conduction velocity (SNCV), motor nerve conduction velocity (MNCV), and complex muscle action potential (CMAP) amplitude were elevated in both groups following treatment (P < 0.05). Relative to the control group, the study group had higher values of SNCV, MNCV, and CMAP amplitude at 1, 3, and 6 months following treatment (P < 0.05). Relative to before treatment, the anterior–posterior diameter of the median nerve in the cross section of the hamate bone in both groups was longer after treatment (P < 0.05), and the transverse area of the median nerve in the cross section of the lenticular bone and the thickness of the transverse wrist ligament were smaller at 1, 3, and 6 months following treatment (P < 0.05). Nevertheless, there were no differences in the changes of the above ultrasound examination parameters between the two groups after treatment (P > 0.05).ConclusionUltrasound-guided acupotomy + PRP therapy has effective clinical efficacy in the treatment of CTS, which can alleviate the degree of pain, improve wrist joint function, promote the activities of daily living, reduce the incidence of complications, and improve the median nerve conduction.